How do professional learning communities aid and hamper professional learning of beginning teachers related to differentiated instruction?. Issue 3 (3rd April 2017) - De Neve, Debbie; Devos, Geert
Abstract: Research has shown that adequate support from the school environment is necessary to help beginning teachers in applying differentiated instruction (DI), but how schools can aid in this process remains unclear. This qualitative study explores how professional learning communities (PLCs), an indicator of a supportive school environment, can enhance beginning teachers' professional learning in DI. Furthermore, it examines how structural and cultural school conditions foster the development of PLCs in the schools' organization. Semi-structured interviews were conducted with school leaders, special needs coordinators, and beginning teachers in primary schools. A comparative analysis was carried out in three schools with high (case A), medium (case B), and low (case C) levels of beginning teachers' professional learning in DI, as assessed by changes in practice (i.e. teachers' flexibility in adapting their classroom behaviour). The comparative analysis indicated that the three cases could be situated at different stages of PLC development. Case A had reached the mature stage, whereas case B was in the evolving stage and case C was still in the beginning stage of PLC development. Also, the analysis indicated that structural and cultural school conditions in the three cases were related to the different stages of PLC development. Finally, the results revealed that in the three cases, leadership of both the principal and special needs coordinator played a key role in the development of the structural and cultural school conditions.